2005
DOI: 10.1016/j.ejpain.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of blood flow response in the trapezius muscle following needle stimulation (acupuncture) between healthy subjects and patients with fibromyalgia and work‐related trapezius myalgia

Abstract: Needle stimulation (acupuncture) has recently been shown to increase blood flow in the tibialis anterior muscle and overlying skin in healthy subjects (HS) and patients with fibromyalgia (FM). The aim of the present study was to examine the effect of needle stimulation on local blood flow in the trapezius muscle and overlying skin in HS and two groups of patients suffering from chronic pain in the trapezius muscle, i.e., FM and work-related trapezius myalgia (TM) patients. Two modes of needling, deep muscle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 50 publications
6
87
0
1
Order By: Relevance
“…Impaired blood flow to the pain region has been observed in persons with both chronic regional and widespread pain during various provocations, e.g., cold water, needle stimulation by acupuncture, and static or dynamic contractions (Acero et al 1999;Larsson et al 1999;Sandberg et al 2005;Elvin et al 2006;; for comprehensive reviews on this topic see Passatore and Roatta (2006) and Vierck (2006).…”
Section: Insufficient Blood Flow Regulation In Chronic Muscle Painmentioning
confidence: 99%
“…Impaired blood flow to the pain region has been observed in persons with both chronic regional and widespread pain during various provocations, e.g., cold water, needle stimulation by acupuncture, and static or dynamic contractions (Acero et al 1999;Larsson et al 1999;Sandberg et al 2005;Elvin et al 2006;; for comprehensive reviews on this topic see Passatore and Roatta (2006) and Vierck (2006).…”
Section: Insufficient Blood Flow Regulation In Chronic Muscle Painmentioning
confidence: 99%
“…Several studies have shown that acupuncture can be a useful modality for treating pain due to muscle spasms (Lundeberg et al, 1988: Sandberg et al, 2005: Inoue et al, 2006. It is believed that shoulder stiffness is caused primarily by restriction of blood flow to the working muscles where accumulated metabolites appear to activate sympathetic vasoconstrictors.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that shoulder stiffness is caused primarily by restriction of blood flow to the working muscles where accumulated metabolites appear to activate sympathetic vasoconstrictors. Acupuncture stimulation (AS) is reported to increase local tissue blood flow in animals (Noguchi et al, 1999;Sato et al, 2000;Uchida et al, 2007) and humans (Sakai 2005;Sandberg et al, 2003;Sandberg et al, 2005) and are applicable in therapeutic interventions of shoulder stiffness. The effects of acupuncture include neural, endocrinological, cardiovascular, and immunological functions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, trophotherapy and pharmacotherapy 3) , physical therapy using massage 4) , acupuncture, and moxibustion or electrotherapy treatment 5 ) . Balneotherapy, which is a commonly used thermotherapy, has good prospects as a useful treatment for essential chronic shoulder-neck pain, because it has an underlying effect on the systemic circulation 6) .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to muscle tension, previous studies have measured muscle hardness using various types of devices to identify the level of tension in the trapezius, because the hardness is thought to be closely related to the subjective symptoms 16) . For blood circulation analysis, direct measurement of dynamic flow using Laser-Doppler flowmetry 5,17) and non-invasive measurement of total hemoglobin volume and tissue oxygen saturation using nearinfrared spectroscopy (NIRS) have been reported 18) . To quantify pain intensity, the relationship between subjective symptoms and pressure pain has previously been used 19) .…”
Section: Introductionmentioning
confidence: 99%